Предмет: Математика,
автор: Аноним
Упростить СРОЧНОООО
a+b+2√ab/√a+√b
Ответы
Автор ответа:
0
(√a+√b)(a-√ab+b)/(√a+√b) -√ab=a-√ab+b -√ab=(√a-√b)²
(√a-√b)² :(a-b)=(√a-√b)²/(√a-√b)(√a+√b)=(√a-√b)/(√a+√b)
(√a-√b)/(√a+√b)+ 2√b/(√a+√b)=(a√-√b+2√b)/(√a+√b)=(√a+√b)/(√a+√b)=1
(√a-√b)² :(a-b)=(√a-√b)²/(√a-√b)(√a+√b)=(√a-√b)/(√a+√b)
(√a-√b)/(√a+√b)+ 2√b/(√a+√b)=(a√-√b+2√b)/(√a+√b)=(√a+√b)/(√a+√b)=1
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: erkosh47
Предмет: Биология,
автор: lizavozdaeva786
Предмет: Биология,
автор: Алина5357
Предмет: История,
автор: boryakazakevic